IMPLEMENTASI MANAJEMEN LINGKUNGAN DALAM PENGOLAHAN LIMBAH ORGANIK MENJADI ECO ENZYME DI TINGKAT RUMAH TANGGA DI WONOMULYO - Sucianti Sukiana Sari,; Samsul Bahri,; Resky Faradibah Suhab, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Household waste, particularly organic waste such as food and vegetable scraps, remains an environmental problem that has not been optimally addressed in Wonomulyo District, West Sulawesi. Most of this waste is managed conventionally through incineration or landfill disposal, which has negative impacts on the environment. One solution that is starting to be introduced is eco-enzyme—a product produced by fermenting organic waste with sugar and water—which has various ecological benefits, such as acting as a natural cleaner and liquid fertilizer. This study aims to explore the practice of processing organic waste into eco-enzyme at the household level and identify supporting factors, barriers, and impacts. A descriptive qualitative approach was used through case studies of three key informants: an active housewife, a novice, and an environmental cadre. The results indicate that the eco-enzyme implementation process is influenced by community training, social support, and the availability of raw materials. Positive impacts include a 50% reduction in waste volume, reduced chemical use, and increased community ecological awareness. However, challenges remain in the form of limited technical knowledge and limited availability of fermentation materials. This study recommends integrating the eco-enzyme program into local environmental policies based on community participation.